Weak Electron–Phonon Coupling and Enhanced Thermoelectric Performance in n‐type PbTe–Cu2Se via Dynamic Phase Conversion. Issue 1 (10th November 2022) - Wu, Ming; Cui, Hong‐Hua; Cai, Songting; Hao, Shiqiang; Liu, Yukun; Bailey, Trevor P.; Zhang, Yinying; Chen, Zixuan; Luo, Yubo; Uher, Ctirad; Wolverton, Christopher; Dravid, Vinayak P.; et al.
Abstract: This study investigates Ga‐doped n‐type PbTe thermoelectric materials and the dynamic phase conversion process of the second phases via Cu2 Se alloying. Introducing Cu2 Se enhances its electrical transport properties while reducing its lattice thermal conductivity (κlat ) via weak electron–phonon coupling. Cu2 Te and CuGa(Te/Se)2 (tetragonal phase) nanocrystals precipitate during the alloying process, resulting in Te vacancies and interstitial Cu in the PbTe matrix. At room temperature, Te vacancies and interstitial Cu atoms serve as n‐type dopants, increasing the carrier concentration and electrical conductivity from ≈1.18 × 10 19 cm −3 and ≈1870 S cm −1 to ≈2.26 × 10 19 cm −3 and ≈3029 S cm −1, respectively. With increasing temperature, the sample exhibits a dynamic change in Cu2 Te content and the generation of a new phase of CuGa(Te/Se)2 (cubic phase), strengthening the phonon scattering and obtaining an ultralow κlat . Pb0.975 Ga0.025 Te‐3%CuSe exhibits a maximum figure of merit of ≈1.63 at 823 K, making it promising for intermediate‐temperature device applications. Abstract : A novel dynamic phase conversion is observed after Cu2 Se alloying in Ga‐doped n‐type PbTe. Cu2 Se alloying results in the Cu2 Te and tetragonal CuGa(Te/Se)2 precipitates, leading to enhanced carrier concentration. With increasing temperature, the sample exhibits the dynamic change in Cu2 Te content and the generation of cubic CuGa(Te/Se)2, obtaining an ultralow κlat and a high ZT of ≈1.63.